Riviera. Season three [videorecording (DVD)] - Jordan, Neil, 1950-; McGuinness, Paul; Eshkeri, Ilan (Universal Studios Home Entertainment, 2021)
A year has passed since the explosive finale of Riviera Season Two. Georgina has abandoned the Riviera and reinvented herself as Georgina Ryland. She has partnered up with charismatic art restitution expert, Gabriel Hirsch, and together they scour the world for stolen artworks. However, when Gabriel confiscates an artifact from a corrupt dealer, this catapults them into a dangerous conspiracy. From Venice, they travel to Saint-Tropez and Buenos Aires in pursuit of the truth.